Water and other fluids in nephrolithiasis: State of the art and future challenges. Issue 5 (24th March 2017) - Ticinesi, Andrea; Nouvenne, Antonio; Borghi, Loris; Meschi, Tiziana
ABSTRACT: Adequate hydration, as to maintain urinary volume over 2 L/day, has long been considered as the cornerstone medical prescription for preventing nephrolithiasis. However, scientific evidence about what kind of water stone formers should drink and about the effects of other beverages on urinary stone risk factors is sometimes unclear. Moreover, the recommendation that water therapy prevents kidney stone recurrence relies on only one randomized controlled trial, even if more epidemiologic and basic science studies seem to support this assumption. Therefore, in this review we analyze current evidence that support water therapy in nephrolithiasis and we highlight the possible effects of different types of water and other beverages on lithogenic risk, giving some practical recommendations for what stone formers should be advised to prevent recurrence.